USING HYPNOTEACHING STRATEGY TO MOTIVATE STUDENTS TO LEARN ENGLISH AT SMAN 7 MAKASSAR - Ilyas, Sukma; Dollah, Syarifuddin; Munir, Munir (State University of Makassar, 2022)
The objective of this research was to find out whether the use of hypnoteaching strategy motivate the student to learn English. This research took place at SMAN 7 Makassar. The population of this research was the student of SMAN 7 Makassar. The researcher used a simple random sampling technique. The instrument of this research was questionnaire which was administered as a pretest and posttest. Based on the result of the mean score, the researcher found that the use of hypnoteaching strategy can motivate the students to learn English. It was proved by the result of the posttest which was higher than the result of the pretest (38.63 >89.60). Then, the researcher concluded that the use of hypnoteaching strategy motivates the students to learn English.Keywords: Hypnoteaching strategy, students’ learning motivation